2017
DOI: 10.1111/petr.13066
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and improved left ventricular mass index in children after renal transplantation

Abstract: This study was conducted to evaluate the changes in BP and LVH after the transplantation and to evaluate the effect of BP changes in LVH. Forty-three pediatric renal transplant patients, with a mean age of 16.99 ± 3.88 years, were enrolled in this study. Twenty-three (53.5%) of the patients were male. Medical records for pretransplantation period (closest to the time of transplantation) and for post-transplantation period (9-12 months after transplantation) were reviewed. All the patients had BP measurements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…39,40 Previous studies largely used a crude measure of LVH prevalence as the observed outcome, rather than examining continuous changes in LVM index over time. 40 Studying a continuous measurement is especially important in children, as cutoffs for LVH using LVM index in children with chronic kidney disease have the potential for over- or underestimated LVH prevalence. 41 Our study has extended existing findings by determining that changes seen in the first several years after transplantation, as measured using LVM index scores as a continuous variable over time rather than a discrete cutoff value, are sustained up to 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Previous studies largely used a crude measure of LVH prevalence as the observed outcome, rather than examining continuous changes in LVM index over time. 40 Studying a continuous measurement is especially important in children, as cutoffs for LVH using LVM index in children with chronic kidney disease have the potential for over- or underestimated LVH prevalence. 41 Our study has extended existing findings by determining that changes seen in the first several years after transplantation, as measured using LVM index scores as a continuous variable over time rather than a discrete cutoff value, are sustained up to 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with CKD have LVH, and several studies have reported that LVH was improved after KT (7)(8)(9)(10)(11)(12). Reportedly, the presence of LVH was independently associated with an increased risk for graft dysfunction and future CVD in patients receiving KT (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is an important risk factor for the development of LVH and is closely linked with body fluid volume (19,20). Although there are several studies on changes in BP after KT, the presence of hypertension and changes in BP were evaluated by various methods (11,12,(21)(22)(23)(24). Some studies reported that BP decreased after KT (11,(21)(22)(23), but others reported that BP rather increased after KT (12,24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations